THE CHURCH SLAVONIC LANGUAGE - Mishlanov, V.A. (Perm Federal Research Centre Journal, 2016)
It is shown in the article that the medieval Church Slavonic-Russian diglossia is preserved in the modern Russian literary language. The church religious style of the Russian language forms sort of the transitional space between literary styles of the Russian language genetically based on Church Slavonic, both lexically and syntactically, and the mere Church Slavonic (liturgical) language.